Influence of the system of royalties in the department of Boyacá (2014)
The mandate of the Lord President Juan Manuel Santos in its 2010-2014 development plan called "prosperity for all" within its sustainable growth and sustainability program has implemented the engines for growth and job creation that seeks economic and social development status within the mining and energy sector found mine development and expansion energy using economic considerations as tools generated by the mining operations.